Stress Study on Retirement of Secretariat Employees of South Bengkulu Regency - Mulyadi Mulyadi (Penerbit Jurnal Indonesia, 2022)
The purpose of this research is to study the stress that usually occurs in facing retirement. This research method is a qualitative descriptive method and direct interviews. The purpose of this study was to analyze the stress faced by retirees. The results of this study indicate that employees who enter retirement experience changes in life psychologically.